THE ROLE OF THE OFFICE OF WOMEN'S EMPOWERMENT, CHILD PROTECTION, POPULATION AND FAMILY PLANNING IN HANDLING CASES OF SEXUAL VIOLENCE AGAINST WOMEN IN THE PROVINCE OF BANTEN - Sarfina Darajat; Qotrun Nida; Ria Yuni Lestari (Journal Civics And Social Studies, 2023)
Sexual violence against women that occurred in Banten Province has become a public concern lately so that prevention efforts must be increasingly considered to the community, especially to women, therefore this study aims to determine the role of the Banten Province Office of Women's Empowerment, Child Protection, Population and Family Planning (DP3AKKB) in handling cases of sexual violence against women. This research was conducted in the Banten Provincial Government Center Area (KP3B) Jl. Syech Nawawi Al-Bantani Palima Curug, Sukajaya, Serang, Banten and UPTD PPA Banten Province on Jl. Ki Ajurum No.4, Cipocok Jaya, Kec. Cipocok Jaya, Serang City, Banten using a qualitative approach method. Data collection using observation, interviews and documentation. The results found that DP3AKKB plays a very important role as a facilitator in overcoming cases of sexual violence against women in Banten Province. UPTD PPA plays a role in overcoming cases of sexual violence against women from the process of reporting cases, health referrals, legal aid assistance, psychological recovery of victims, escorting to the police, until the case is resolved. DP3AKKB is also a place for education and dissemination of women's rights. Based on the results of the research conducted, it can be concluded that the role of the agency is very important to reduce cases of sexual violence against women with the handling that has been determined by DP3AKKB and UPTD PPA as a community service in handling cases of sexual violence against women. The number of people who report is the success rate of the agency in handling sexual violence against women, because the more victims who report, the greater the level of public awareness in fighting for women's rights for a more comfortable and safe life.